Impacto da radiofrequência fracionada microablativa na saúde vaginal, microbiota e celularidade de mulheres pós-menopausadas - Sarmento, Ayane Cristine Alves (2020)
The aim of study was to evaluate the effects of microablative fractional radiofrequency (MAFRF) as a possible option in the non-hormonal treatment of symptoms from menopause. We studied 55 healthy postmenopausal women before and after treatment regarding vaginal health index (VHI), vaginal microbiota, vaginal pH, and cell maturation. Three applications of MAFRF were performed in the vagina/vaginal introitus. During the whole treatment, six vaginal smears were obtained and stained by the Papanicolaou technique for determining the degree of maturation of the vaginal epithelium, as well as stained according to the Gram procedure for classification of vaginal flora, following the criteria of Spiegel. For vaginal pH determination, the pH indicator strips were applied against the vaginal wall. Statistical analysis was performed using SPSS for Windows (version 17.0). Data presented were reported as mean ± standard deviation. Differences were analyzed using the statistical method of generalized estimation equations with autoregressive correlation structure "1" and robust standard errors. The mean age was 59.8 ± 4.2 years, and the time of menopause was 15.4 ± 4.5 years. After treatment, there was an increase in the percentage of lactobacilli (p<0.001). Consequently, there was a progressive decrease in vaginal pH during the treatment (p<0.001). Regarding cell maturation, there was a decrease in the percentage of parabasal cells (p=0.001) and an increase in the percentage of superficial cells (p<0.001). Additionally, there was also improvement in the VHI index. The mean values of the VHI before and after treatment were 13.2 ± 5.6 and 22.5 ± 3.7, respectively (p<0.001).